2021
DOI: 10.3390/w13162146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dam Construction in the Wang River on Sediment Regimes in the Chao Phraya River Basin

Abstract: The Wang River is one of the major tributaries of the Chao Phraya River (CPR) system in Thailand as the key riverine sediment source supplying the Chao Phraya Delta that has experienced severe shoreline retreat in the past six decades. Historical and observed river flow and sediment data measured during 1929–2019 were used to assess the variation in total sediment load along the Wang River and evaluate the effects of three major dam constructions on sediment supplied from the Wang River to the CPR. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Moreover, the dam caused only about a 5% reduction of sediment supply from the Ping River to the CPY River system (Namsai et al, 2021). Charoenlerkthawin et al (2021) reported that the construction of three large dams in the Wang River system (Figure S4a) also did not cause a significant change in sediment load supply to the CPY River. The observed sediment loads downstream of the dams increased significantly due to additional sediment sources downstream of each dam.…”
Section: Shoreline Recession Has Also Reduced Noticeably Since 2002mentioning
confidence: 99%
“…Moreover, the dam caused only about a 5% reduction of sediment supply from the Ping River to the CPY River system (Namsai et al, 2021). Charoenlerkthawin et al (2021) reported that the construction of three large dams in the Wang River system (Figure S4a) also did not cause a significant change in sediment load supply to the CPY River. The observed sediment loads downstream of the dams increased significantly due to additional sediment sources downstream of each dam.…”
Section: Shoreline Recession Has Also Reduced Noticeably Since 2002mentioning
confidence: 99%
“…The high rate of land subsidence (13-150 mm/y) due to overuse of groundwater has been reported as a major factor responsible for critical shoreline retreat in the CPD [12,13]. The construction of large dams in the Chao Phraya River system did not reduce the riverine sediment supply to the CPD [23][24][25][26]. Various hard/grey solutions have been applied along the WCPD and ECPD coasts to protect these major commercial and economic areas over the last 30 years [11].…”
Section: Study Areamentioning
confidence: 99%
“…The Chao Phraya Delta (CPD), the largest delta and low-lying muddy coast in Thailand, has experienced shoreline recession for over six decades due to relative sea-level rise [24][25][26][27][28][29] . With an average shoreline retreat rate during 1996-2002 of more than − 16 m/y, the CPD has become one of the world's shoreline retreat hot spots 30 .…”
Section: Introductionmentioning
confidence: 99%